DEVELOPMENT AND VALIDATION OF RP-CHIRAL HPLC METHOD FOR QUANTIFICATION OF (S)-ISOMER IN TENOFOVIR DISOPROXIL FUMARATE - Bodempudi, Suresh Babu; Rupakula, Ravi Chandra Babu; Reddy, Konda S. (International Journal of Current Pharmaceutical Research, 2017)
Objective: The main objective of present study was to develop and validate a reverse phase enantioselective chiral high performance liquid chromatographic method was developed for enantiomeric resolution of Tenofovir disoproxil fumarate; it decreases the HIV infection in human body. The method is specific, rapid, precise and accurate for the separation and determination of (S)-isomer in tenofovir disoproxil fumarate drug substance form. Methods: The S-Isomer of Tenofovir disoproxil fumarate was resolved on a Chiral AGP (150 × 4.0 mm, 5 µm) column (L-41) using a mobile phase system containing 0.1 M ammonium acetate in water pH 6.8 with ammonia solution and methanol in the ratio of (85:15 v/v). The mobile phase was set at a flow rate of 0.8 ml/min and the volume injected was 10μl for every injection. The detection wavelength was set at 260 nm and the column temperature was set at 15 °C. Results: The proposed method was productively applied for the quantitative determination of (S)-isomer in Tenofovir disoproxil fumarate drug substance form. The linear regression analysis data for calibration plots showed a good linear relationship over a concentration range of 0.125 to 3.75 µg/ml for (S)-isomer, 0.125-3.75 µg/ml for Tenofovir disoproxil fumarate. The mean values of the correlation coefficient were 0.999 and 0.999 for (S)-isomer and Tenofovir disoproxil fumarate. The method was validated as per the ICH guidelines. The detection limit (LOD) was about 0.05 µg/ml and quantitation limit (LOQ) was about 0.125 µg/ml for (S)-isomer and Tenofovir disoproxil fumarate. The relative standard deviation was found to be 0.78 % for (S)-isomer in Tenofovir disoproxil fumarate. Conclusion: The developed and validated HPLC method and the statistical analysis showed that the method is repeatable and selective for the estimation of the (S)-isomer of the Tenofovir disoproxil fumarate drug substance.